Politik Hukum Undang-Undang Pemilihan Presiden 2009 - Mirza Satria Buana (Fakultas Hukum Universitas Islam Indonesia, 2009)
Normatively, an act, in whatever form in may be, shall be based on the orientation for the the people benefit and to ascertainment of the justice for people. The politics of law of presidential election issued by the relevant body is considered to be conservative and tends to be elitical. On theother hand, the success of Indonesia to exit fron the transition of democracy is determined by the lagal policiy of the govenrment. Through the issuance of act on Presidential election which is responsive, a better and more democratic new president may be ekected.Keywords : Democracy, Politics Of Law, Presidential Election